Design And Development Of Water Tunnel For Flow Visualization Study On Micro-Hydrokinetic Turbine - Tong, Poh Eng (Universiti Sains Malaysia, 2018)
A water tunnel is an experimental facility utilized for testing the hydrodynamic behavior of submerged bodies in flowing water. Water tunnel can be designed and developed to visualize a wide range of flow and one of its ability is to visualize the flow behavior over different objects and structures hence studying the phenomenon of boundary layer such as the vortex induced, flow separation, turbulence and the others. For the current project, a micro-hydrokinetic turbine model is to be placed in the test section of the water tunnel to visualize and study the flow behavior around the model. Hence a water tunnel that capable to mimic and simulate the Malaysia river flow velocity conditions (0 – 0.6